Revisão sistemática sobre sistemas caseiros de sinais - Almeida, Antonia Rivalda Gomes de (Brasil, 2024)
This article's main focus was to conduct a survey of theses and dissertations in the Capes Theses and Dissertations Bunch and in the Brazilian Digital Library of Theses and Dissertations (BDTD) to compose a systematic review on homesign systems. The research was based on the following objectives: searching in the databases of theses and dissertations for stricto sensu postgraduate academic productions that deal with homesign systems or related terms; and, analyze academic productions that discuss homesign systems or related terms. To meet this proposition, a systematic review of a mixed nature with qualitative convergence was carried out, in which quantitative and qualitative data were selected with the aim of carrying out a conceptual review on the topic. The results showed that the most used terminology is homesign language; that the works consider these communication systems as a language, even given their existential joviality; and that only rural cases the academy has to focus on.